Penerapan LKS Berbasis Inkuiri Terbimbing Pada Materi Listrik Terhadap Hasil Belajar Siswa Kelas IX SMPN 22 Kota Jambi - Chuznul Chotimah; Menza Hendri; Dian Pertiwi Rasmi (Jurnal Penelitian Pembelajaran Fisika, 2018)
This study purpose to find out the student learning outcomes of cognitive aspects by applying guided inquiry based LKS with the help of PhET Interactive Simulations better than the conventional LKS used by schools on the subject of static electricity and dynamic electricity. This research is a quantitative research with Quasy Experimental design and the design of non-equivalent control group design. The population in this study is the students of class IX SMPN 22 Kota Jambi consisting of 5 classes. The sample used in this research is class IX C and as experimental class and class IX D as control class. The experimental class is taught by using guided inquiry LKS and control classes taught with the school's conventional LKS. Research instruments are objective questions that have been tested. This study collected data using multiple choice questions that have been tested in IXA SMPN 16 Muaro Jambi class. The results showed that the average value of the experimental class is 32.62 and the control class is 31.18. obtained the results of research that the value of t is greater than the value ttable with a significance of 0.05. Based on research that has been done tcount equal to 1.71. while the ttable is 1.67. because tcount obtained 1.71 ≥ 1.67 then H0 rejected. This shows that there are differences in cognitive learning outcomes of students using instructional based LSM inquiry with the help of PhET Interactive Simulations and LKS conventional schools.